STUDI TENTANG PRESTASI BELAJAR MAHASISWA TUNADAKSA DI UNIVERSITAS RIAU - Salmon Simanjuntak; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted on the campus of University of Riau on the students’ quadripleqic. The purpose of this study is to determine the motivation of college students to the lecture and to know the obstacles and limitations of college students in achieving a good learning achievement and how college students overcome these obstacles. This research was conducted on 5 students from 3 different faculties, namely FISIP, FKIP, and FAPERIKA. Data collection techniques used using observation, interviews, and documentation. This research uses qualitative descriptive analysis technique. Research conducted found that the motivation that pushed the 5 college students for the lecture consisted of internal factors and external factors. Internal factors are they are not pessimistic with the condition, and for external factors researchers found several factors, namely; (1) parental support, (2) better future / life pland, (3) bidisuises scholarship, (4) specialization majors / interest major, (5) high confidence, (6) do not want to like friends in village which is not lecture and his life is not clear (so burden with his parents). For the obstacles they encounter, each student has different obstacles, depending on his condition and. Researchers found that the 5 student are able to overcome the obstacles they encounter obstacles, although to overcome these obstacles they are very dependent on others.Keyword: College Sudents, Obstacles